Extra-alveolar miniscrews: are all brands similar? - Borsato, Karina Tostes [UNESP]; Bernardino, Raissa Mariele [UNESP]; Campos, Lucas Arrais; Bento, Daniela Águida; Vaz, Luiz Geraldo [UNESP]; Gandini Júnior, Luiz Gonzaga (FapUNIFESP (SciELO), 2025)
Introduction: Awide variety of extra-alveolar orthodontic minis-crews are available. Objective: This study aims to describe and compare the design, and the topographical and mechanical properties of five distinct commercial brands of extra-alveolar minis-crews. Methods: Scanning electron microscopy (SEM), using 25×, 50×, 100×, and 200× photomicrographs, and in-vitro mechanical tests (driving torque, torsion, and pullout test) to compare ex-tra-alveolar miniscrews (n=80, 2 mm x 12 mm) from the following brands: Bioray, DatSteel, Morelli, OBS, and Peclab. Results: De-spite the 2 × 12 mm screw size, only the Morelli and Peclab minis-crews actually measured 12 mm in thread length. The studied brands revealed different thread characteristics (i.e., thread pitch and minor/major diameter). The Morelli miniscrews presented the smallest thread pitch and, consequently, the largest number of threads. Bioray, DatSteel, and OBS miniscrews presented a trapezoidal thread shape, while the others were triangular. SEM showed adequate polishing on the Morelli, OBS, and Peclab miniscrews. The insertion torque was higher than the removal torque for the DatSteel, Morelli, and OBS miniscrews during the driving torque test of the first four threads. The same result occurred with Morelli miniscrews during the driving torque test of the full screw. The resistance limits recorded in the pullout tests were significantly higher than the maximum force used in orthodontic tooth movement. The findings showed no significant differences between the results of the titanium and steel miniscrews. Conclusions: The five types of miniscrews studied presented different characteristics, so the clinician must consider the correct size, number of threads, length, polishing surface, and metallic alloy when choosing the appropriate miniscrew for an application.
Keywords: Corrective Orthodontics; Mechanical tests; Microscopy, Electron, scanning; Orthodontic anchorage procedures